TOOTH REGENERATION - A REVIEW - .K, Ashwini; Somasundaram, Jayalakshmi; Sivaswamy, Vinay (International Journal of Psychosocial Rehabilitation, 2020)
Introduction: Dental problems caused by caries, PDL disease, and injury to the tooth compromise oral health issues resulting in loss of tooth, thereby affecting the quality of human life. There are several artificial therapies introduced into dentistry to compensate for the loss of tooth structure and avulsed tooth structures, i.e., inorganic fillings, RCT, RPD, FPD, CD, and even implants. They tend to fail at times. The current advances in dentistry include regenerative therapy, stem cell biotechnology, and tissue engineering for 3D scaffolds. In this review, we focus on the recent findings and technologies relevant to whole teeth regenerative therapy. Materials and methods: The articles and journals pertaining to this topic were searched over Pubmed, Google Scholar, Semantic Scholar, MeSH Core, Elsevier, and Medline. Articles related to tooth regeneration, stem cell-based regeneration, and scaffolds were included. Wherein articles irrelevant to these topics are excluded. The data was collected from 2000 to 2020. Discussion: Regenerative therapies for whole tooth regeneration are a novel therapeutic concept. Dental stem cells and activating cytokines have a candidate approach for tooth regeneration and the potential to differentiate tooth regeneration in vitro or in vivo and form a functional tooth. 3D tissue engineering for the bioengineered scaffolds regenerates organogenesis. They have several biomedical applications and have high bioactivity. A bioengineered tooth was also able to perform the same functions as a physiological tooth. The stem cells play an efficient role in the formation of tooth structures too. Conclusion: Though tooth embryogenesis takes a longer duration, it is highly effective and promotes mental well-being. There is also huge potential for 3D printing of tissue engineering. Tooth regenerative therapy is actually a future regenerative technology.